The Impact of Corporate Governance of Banks on Stock Market Performance during COVID-19 Pandemic: Evidence from Johannesburg Stock Exchange Using PLS-SEM Approach - Bentaib, Asma; Lamoudi, Mohammed Tahar (Finance and Business Economies Review, 2023)
The paper aims to analyse empirically the impact of internal mechanisms of corporate governance of banks on stock market performance, employing six corporate governance mechanisms to examine their impact on five market performance measures. The statistical sample of the study included the eight listed banks on the Johannesburg Stock Exchange for the selected period of 2019-2022. To this end, a PLS-SEM approach was employed using SmartPLS v.4 software package. Our empirical results indicate that mechanisms of corporate governance of banks had a significant positive impact on JSE performance during the Covid-19 crisis, suggesting that corporate governance may have moderated the adverse effect of the financial crisis on the stock market performance. These striking results can be attributed to and validate the argument that effective internal corporate governance practices could improve stock market performance during pandemics and crises.